Bilateral asymptomatic common carotid artery stenosis: Mouse model for stroke research - Achmad Firdaus Sani, - (Faculty of Veterinary Medicine, University of Tripoli, 2022)
Background: Asymptomatic carotid artery stenosis has become more prevalent worldwide and is often associated with a poor prognosis. Numerous guidelines highlighted surgical interventions as treatment for carotid artery stenosis, but only a few recommendations were made regarding non-surgical interventions due to its limited data. Aims: This study aims to develop a mice model for research in non-surgical interventions of asymptomatic carotid artery stenosis. Methods: Adult male Rattus norvegicus, Wistar strain models with bilateral asymptomatic common carotid artery stenosis (BACAS) were created by ligating the common carotid artery with a 0.6 mm diameter needle and then removing the needle. The mice’s body weight, clinical signs and symptoms, and post-mortem brain analysis were compared between the sham-operated group and the BACAS group. Results: The mortality rate among the BACAS group is 11.11%. There is no significant difference in mean body weight before surgery, after the observation period, and percentage of weight decrease between sham-operated and BACAS groups (p = 0.710, 0.632, and 0.806, respectively). None of the surviving mice in this study exhibit signs of motor paralysis. Gross examination of the brain reveals no signs of infarction or hemorrhage. Conclusion: We have established a novel BACAS mouse model which is cost-efficient, easy to produce, and with no significant alteration in body weight, clinical parameters, and brain morphology.